2004
DOI: 10.1177/0272989x03261565
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Sibutramine in the Treatment of Obesity

Abstract: Sibutramine is a cost-effective treatment for obesity when combined with diet and lifestyle advice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(74 citation statements)
references
References 19 publications
1
73
0
Order By: Relevance
“…One study included in the NICE review of a pharmacological trial for sibutramine included diet and exercise advice as the control arm with a cost of £243.48 per person. 92 Avenell and colleagues 30 reviewed treatment for obesity and constructed an economic model for a diet and exercise intervention for individuals with impaired glucose tolerance. The total estimated cost for the LI was £324 per person in the first year and £178 per person for subsequent years.…”
Section: Other Issues and Methodological Concernsmentioning
confidence: 99%
“…One study included in the NICE review of a pharmacological trial for sibutramine included diet and exercise advice as the control arm with a cost of £243.48 per person. 92 Avenell and colleagues 30 reviewed treatment for obesity and constructed an economic model for a diet and exercise intervention for individuals with impaired glucose tolerance. The total estimated cost for the LI was £324 per person in the first year and £178 per person for subsequent years.…”
Section: Other Issues and Methodological Concernsmentioning
confidence: 99%
“…All costs were inflated to 2009 prices using an NHS-specific index. The costs of CVD were taken from Warren et al, 111 and were reported as one-off costs for fatal and non-fatal events, and as an annual cost for survivors. No other costs associated specifically with CVD were included.…”
Section: Costsmentioning
confidence: 99%
“…Treating adult obesity with the drug orlistat costs $8,327 per QALY, 46 the drug sibutramine costs $9,299 per QALY. 47 Gastric bypass surgery costs $5,000-$16,100 per QALY for women and $10,000-$35,600 per QALY for men. 48 Wheeling Walks, a behavior modification program targeted to sedentary adults, costs $14,286 per QALY; other behavior modification programs for adults cost much more per QALY saved.…”
Section: Making Interventions Cost-effectivementioning
confidence: 99%